Retraction: A highly antibacterial polymeric hybrid micelle with efficiently targeted anticancer siRNA delivery and anti-infection in vitro/in vivo. Issue 2 (20th December 2021) - Zhou, Li; Xi, Yuewei; Chen, Mi; Niu, Wen; Wang, Min; Ma, Peter X.; Lei, Bo
Abstract : Retraction of 'A highly antibacterial polymeric hybrid micelle with efficiently targeted anticancer siRNA delivery and anti-infection in vitro / in vivo ' by Li Zhou et al., Nanoscale, 2018, 10, 17304–17317, DOI: ; 10.1039/C8NR03001D .